Overview and evaluation of 15 years of Creutzfeldt-Jakob disease surveillance in Belgium, 1998-2012. Issue 1 (December 2015) - Litzroth, Amber; Cras, Patrick; De Vil, Bart; Quoilin, Sophie
Abstract Background In 1998, following the detection of variant Creutzfeldt-Jakob disease (vCJD) in the UK, Belgium installed a surveillance system for Creutzfeldt-Jakob disease (CJD). The objectives of this system were to identify vCJD cases and detect increases in CJD incidence. Diagnostic confirmation of CJD is based on autopsy after referral by neurologists. Reference centres perform autopsies and report to the surveillance system. The aim of this study was to assess whether the system met its objectives and to assess its acceptability. Methods For 1999–2010, we linked surveillance data with hospital discharge data. We calculated the proportion of CJD suspected patients who died in hospitals and were captured by the surveillance system. We surveyed stakeholders on knowledge of the surveillance system, referral practices and acceptability. We compared proportions using the chi-square test and investigated variables associated with capture using a multivariable logistic regression model. Results On average 60 % of hospitalised patients who died with suspected CJD were captured by the surveillance system. This proportion did not significantly differ over the years (p = 0.1). The odds of capture significantly decreased with every 1 year increase in age (OR = 0.95, 95 % CI 0.92–0.98, p = 0.001). Eleven percent of surveyed neurologists would not refer suspect vCJD cases for autopsy, nor contact a reference centre for diagnostic support. Sixty-one percent of surveyed neurologists were not familiar with the surveillance system. Awareness of the existence of the system did not impact referral behaviour (p = 0.18). CJD and vCJD surveillance were considered important by the majority of stakeholders. Conclusions Although 40 % of the suspect CJD cases were not referred for autopsy, our data suggest that the Belgian CJD surveillance system meets one of its main objectives: it can detect changes in CJD incidence. However, we do not have sufficient evidence to conclude that the system meets its second objective of detecting vCJD cases arising in Belgium. Although not well known, the system was considered acceptable by its stakeholders.